ORGANIZATIONAL AND METHODOLOGICAL BASIS OF THE ADAPTATION OF FOREIGN STUDENTS TO EDUCATIONAL ENVIRONMENT OF UNIVERSITIES OF UKRAINE - Hu, Zhunsi (Educological discourse, 2016)
The article presents the methodological bases and methodical means of adaptation of foreign students to the educational environment of Ukrainian universities. Characterized essence of adaptation of foreign students to the educational environment of universities in Ukraine as a scientific phenomenon. The pedagogical conditions of foreign students for successful adaptation to the educational environment of Ukrainian universities. Disclosure of the contents and structure of foreign students to adapt the program to the educational environment of Ukrainian universities.